Endoscopic characteristics and performance of WASP classification in the diagnosis of colorectal sessile‐serrated lesions in Vietnamese patients - Nhu Thi Hanh Vu; Huy Minh Le; Diem Thi‐Ngoc Vo; Nhan Quang Le; Dung Dang Quy Ho; Duc Trong Quach (JGH Open, 2024)
Abstract Background/Aims Sessile‐serrated lesions (SSLs) are challenging to detect due to their typically subtle appearance. The Workgroup serrAted polypS and Polyposis (WASP) classification was developed to diagnose SSLs endoscopically. This study aimed to evaluate the endoscopic characteristics of SSLs and the performance of the WASP classification in the Vietnamese population. Methods This cross‐sectional study was carried out on patients with lower gastrointestinal symptoms who underwent colonoscopy at a Vietnamese tertiary hospital. Univariate and multivariate analyses were performed to identify endoscopic features associated with SSLs. The performance of the WASP classification for diagnosing SSLs was assessed, and SSLs were diagnosed according to the 2019 World Health Organization (WHO) criteria. Results There were 2489 patients, with a mean age of 52.1 ± 13.1 years and a female‐to‐male ratio of 1:1.1. A total of 121 specimens from 105 patients were diagnosed with SSLs. According to multivariate analysis, the endoscopic features significantly associated with SSLs were proximal location (odds ratio [OR]: 2.351; 95% confidence interval [CI]: 1.475–3.746), size >5 mm (OR: 2.447; 95% CI: 1.551–3.862), flat morphology (OR: 2.781; 95% CI: 1.533–5.044), irregular shape (OR: 4.516; 95% CI: 2.173–9.388), varicose microvascular vessels (OR: 5.030; 95% CI: 2.657–9.522), and dark spots inside the crypts (OR: 5.955; 95% CI: 3.291–10.776). The accuracy of the WASP classification for diagnosing SSLs was 94.0% (95% CI: 92.8%–95.0%). Conclusion Proximal location, size >5 mm, flat morphology, irregular shape, varicose microvascular vessels, and dark spots inside the crypts were significantly associated with SSLs. The WASP classification had high accuracy in the diagnosis of SSLs.